Association between walnut consumption and diabetes risk in NHANES. Issue 7 (11th July 2018) - Arab, Lenore; Dhaliwal, Satvinder K.; Martin, Carly J.; Larios, Alena D.; Jackson, Nicholas J.; Elashoff, David
Abstract: Background: Dietary interventions and cohort studies relating tree nut consumption to blood glucose levels suggest a possible effect of walnuts. Objective: To examine the associations between walnut consumption and diabetes risk using data from the National Health and Nutrition Examination Survey. Methods: National Health and Nutrition Examination Survey data on adults conducting 24‐hour dietary recall was pooled across the years 1999 through 2014. Diabetes status or risk was based on self‐report, medication use, fasting plasma glucose levels, and haemoglobin A1c (HbA1c ) levels. Individuals were characterized based on reported consumption of walnuts, mixed‐nuts, or no nuts. Results: After adjustment for covariates, walnut consumers showed lower risk for diabetes compared with non‐nut consumers based on self‐report (odds ratio of 0.47, 95% confidence interval [CI] 0.31‐0.72) as well as fasting blood glucose (relative risk ratio 0.32, CI 0.17‐0.58) and HbA1c (relative risk ratio 0.51, CI 0.27‐0.99). For each standard deviation of increase in walnut intake, prevalence of diabetes dropped 47%. The gender by walnut interaction suggests that the effect may be more potent among women than men (dose response P  = .061). Conclusions: Both among individuals with known diabetes and those diagnosed based on elevated diabetes blood markers, the prevalence of individuals with diabetes was significantly lower among the walnut consumers. A possible gender‐specific effect invites further attention.